2014
DOI: 10.1212/wnl.0000000000000028
|View full text |Cite
|
Sign up to set email alerts
|

Development of movement-related intracortical inhibition in acute to chronic subcortical stroke

Abstract: Movement-related ICI one week after a subcortical stroke is associated with better outcome of hand motor function. Disinhibition in the ipsilesional primary motor cortex could be a mechanism of how the brain attempts to promote motor recovery after stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
47
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 35 publications
5
47
0
5
Order By: Relevance
“…One simple indicator of functional outcome prognosis is the degree of initial motor impairment [72], however, individual prediction remains difficult due to notable variability in each patient. Newer measures such as the integrity of the corticomotor pathway and ipsilesional cortical activity after stroke obtained with neuroimaging techniques and TMS give rise to additional prognostic values [35,73,74], but it remains to be seen whether they can contribute information on treatment success using FES.…”
Section: Reviewmentioning
confidence: 99%
“…One simple indicator of functional outcome prognosis is the degree of initial motor impairment [72], however, individual prediction remains difficult due to notable variability in each patient. Newer measures such as the integrity of the corticomotor pathway and ipsilesional cortical activity after stroke obtained with neuroimaging techniques and TMS give rise to additional prognostic values [35,73,74], but it remains to be seen whether they can contribute information on treatment success using FES.…”
Section: Reviewmentioning
confidence: 99%
“…There is some evidence that indicates this decrease in GABA A signaling normalizes with recovery (Talelli et al, 2006), although more recent studies have suggested that it is maintained into the chronic phase of recovery after stroke (Blicher et al, 2009;Hummel et al, 2009). Pre-movement SICI in the acute phase is also a predictor of recovery, such that patients who show greater disinhibition are also those who show greater recovery, independent of the initial level of impairment (Liuzzi et al, 2014).…”
Section: A Role For Gaba In Long-term Plasticity?mentioning
confidence: 99%
“…Motor cortex hyperexcitability (such as lithium-induced myoclonus) or inhibition of neocortical excitability (like gabapentin-or pregabalin-induced myoclonus) could cause myoclonus [13]. Increased neuronal excitability has been suggested to enhance the potential of the lesioned brain for adaptive neuroplastic processes [15], change the cortical neuroplasticity [16], facilitate the flow of the motor neuron signals to the subcortical regions [17] and induce muscle jerking. This case report indicates that accurate diagnosis of this rare complication after frontal lobe resection ensures appropriate definition of surgical outcome in patients with intractable epilepsy.…”
Section: Discussionmentioning
confidence: 99%